Ethnomatematics In Typical Crafts Of Kulon Progo, Daerah Istimewa Yogyakarta - Zeny Ernaningsih (Universitas Negeri Makassar, 2021)
Recently only several people know that mathematics and cultures are actually two interrelated. Both can not be separated from human life. The relationship between those two is known as Ethnomatematics. This study aims to find out the mathematical elements that exist in the culture of the Kulonprogo community especially on a variety of customs crafts such as agel, bamboo and batik Geblek Renteng. The data obtained from this research are presented qualitatively which is the result of field studies, interviews and literature studies to describe various mathematical elements found in the customs craft of Kulonprogo. The results of the study explained that there are mathematical elements of space geometry, geometry of bisang, artimatika series and geometry of transformation in a variety of customs crafts of the Kulonprogo. The results of this study is expected to be used as knowledge and learning media for mathematics in elementary to senior high school.